1983
DOI: 10.1128/jvi.45.1.420-427.1983
|View full text |Cite
|
Sign up to set email alerts
|

Hyperproduction of adenovirus type 12 E1B gene product in monkey cells, using a simian virus 40 vector

Abstract: Simian virus 40 recombinant DNAs carrying the adenovirus type 12 EBB gene were constructed, propagated, and packaged in monkey cells. Monkey cells infected with the resulting virus stocks hyperproduced the E1B gene products in more than 80% of the cells as revealed by immunofluorescence. The products were distributed in both the nuclei and the cytoplasm, and a condensed form of fleck structure was observed in the cytoplasm. Polyacrylamide gel electrophoresis of the cell extracts and their immunoprecipitates de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
1983
1983

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…pBR322 DNA sequence has an inhibitory effect on the replication of pBR322-SV40 recombinant DNA in monkey cells, and the recombinant DNA which efficiently replicated in the cells has this sequence deleted (13). The EtA coding sequences may also be inhibitory to propagation of the recombinant DNA since an SV40 recombinant carrying the Adl2 EtB gene (SV-AdElB-B) propagates very efficiently in monkey cells, as described in the following paper (22). It has been suggested that 70 to 100% of full-length SV40 DNA is suitable for packaging (19); however, the efficiency of packaging may differ significantly within the lengths in this range.…”
Section: Discussionmentioning
confidence: 90%
“…pBR322 DNA sequence has an inhibitory effect on the replication of pBR322-SV40 recombinant DNA in monkey cells, and the recombinant DNA which efficiently replicated in the cells has this sequence deleted (13). The EtA coding sequences may also be inhibitory to propagation of the recombinant DNA since an SV40 recombinant carrying the Adl2 EtB gene (SV-AdElB-B) propagates very efficiently in monkey cells, as described in the following paper (22). It has been suggested that 70 to 100% of full-length SV40 DNA is suitable for packaging (19); however, the efficiency of packaging may differ significantly within the lengths in this range.…”
Section: Discussionmentioning
confidence: 90%